Perancangan Aplikasi Pendataan Pengunjung Pos Pelayanan Terpadu Berbasis Web Mengunakan Metode Prototype - Afan Yudho Ardiansyah; Ario Kusumo; Muhammad Rizki (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Nowadays, technology is increasingly sophisticated, and information needs are increasingly diverse in obtaining information. With the development of information technology, many agencies in society have used technology to obtain information quickly and accurately. By using the internet, information can be found anywhere and anytime in seconds. Its particular web technology is one that is highly developed. The web is an information page that is provided via the internet so that it can be accessed throughout the world as long as it is connected to an internet network. Web-based applications are applications developed using HTML, PHP, CSS, JS languages ​​that require a web server and browser to run it, such as Chrome, Firefox or Opera. . Web applications can run on the internet or intranet networks (LAN networks), centralized data and ease of access are the main characteristics that make web applications more desirable and easier to implement in various areas of life.